Current status of microsatellite based genetic diversity in Indian sheep - Harikesh Singh Yadav; Avnish Kumar Bhatia; Reena Arora; B. Prakash (Journal of Livestock Biodiversity, 2025)
A comprehensive review of the genetic diversity of Indian sheep characterized genetically using microsatellite markers has been presented in this manuscript. FAO recommended microsatellite markers have been employed for the genetic characterization of Indian sheep breeds. Of the 39 registered breeds of Indian sheep (Ovis aries), 35 have been characterized using microsatellite markers, either by manual or automated methodologies. Four breeds (Gaddi, Bhakarwal, Poonchi and Tibetan) inhabit the disturbed regions of the country rendering collection of blood samples difficult, and consequently have not been hitherto characterized. The genetic diversity of several lesser known indigenous sheep populations has also been accomplished by microsatellite markers. Few descript and several lesser known sheep breeds/populations are yet to be studied at genetic level. These indigenous genetic resources need to be characterized using a uniform panel of markers and method of evaluation to enable comparison at the national level, in order to facilitate outlining of genetic management and conservation programs for these valuable sheep breeds/populations. This paper attempts to review the entire information to gain a comprehensive insight into the genetic diversity prevalent in our indigenous sheep breeds/populations. Limitations and future prospects of the use of microsatellite markers have also been discussed.